Double-layer coated antirust soft magnetic powder, coating process and magnetic powder core preparation method
Through rotary surface nitriding and rotary chemical vapor deposition technology, a dense double-layer insulating coating film is formed on the surface of soft magnetic powder, which solves the problem of uneven coating in the prior art and improves the anti-rust performance and insulating characteristics.
Patent Information
- Application Number
- CN202411818369.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
AI Technical Summary
The existing double-layer coating technology is difficult to achieve uniform and dense coating on soft magnetic powder cores, especially in high-frequency applications, where the powder particle size is small and the fluidized bed chemical vapor deposition technology is not effective.
Using rotary surface nitriding combined with rotary chemical vapor deposition technology, a dense double-layer insulating coating film was successively prepared on the surface of the soft magnetic powder, including a nitride layer and a SiO2 film.
High-efficiency double-layer coating of soft magnetic powder is achieved, which significantly improves anti-rust performance and insulation characteristics, while simplifying the process flow and reducing the preparation steps.
Smart Images

Figure CN119650236A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of magnetic functional materials, and in particular to a double-layer coated rust-proof soft magnetic powder, a coating process and a method for preparing a magnetic powder core. [Background technology]
[0002] In recent years, with the rapid development of new technologies such as artificial intelligence, the Internet of Things, and 6G, the speed of technological innovation in the electronics industry has also accelerated, and correspondingly higher requirements have been placed on electronic components such as transformers and inductors. The metal soft magnetic powder core has a high resistivity due to the addition of insulating materials, making it suitable for use at high frequencies, and has a wide range of application scenarios in the electronic communications industry. However, if the magnetic powder core is not subjected to additional surface spraying, it is very easy to rust during actual use, thus affecting its performance. However, surface spraying is not environmentally friendly on the one hand, and on the other hand it will add additional processes. Therefore, improving the anti-rust performance of the magnetic powder core itself has also become a research focus for technicians.
[0003] The use of powder surface coating can not only improve the overall insulation performance, but also the dense coating layer can effectively block the contact between magnetic powder and air, thereby improving the rust resistance. A good magnetic powder surface coating should be thin, uniform, and fully covered. In order to improve the rust resistance and achieve full coverage of the magnetic powder, researchers have proposed a double-layer coating method, that is, using different insulating materials to coat the magnetic powder twice. For example, the Chinese invention patent with publication number CN117275927B discloses a rust-proof high-performance soft magnetic powder. During the coating process, the magnetic powder is first nitrided by rotating nitriding, and then further phosphating and coating with a composite acid is used to construct a double-layer coating. However, in fact, if the nitriding layer is dense enough to wrap the magnetic powder, the rarely exposed iron will react with the composite acid to generate phosphate, and the phosphating process cannot be carried out smoothly. Therefore, it is difficult to do this type of double-layer coating in the actual coating process. For example, the Chinese invention patent application with publication number CN109979701A discloses a double-layer inorganic insulating coated soft magnetic powder. First, a transition oxide layer is generated on the surface of the magnetic powder by a high-temperature oxidation reaction, and then an inorganic oxide layer is deposited on the surface of the magnetic powder by fluidized bed chemical vapor deposition. This method can introduce a high-density coating layer, but the fluidized bed chemical vapor deposition technology is more suitable for coating particles with a powder particle size of more than 30μm. In order to reduce eddy current losses, soft magnetic powder cores used at high frequencies usually use fine powders with small particle sizes. The fluidized bed chemical vapor deposition technology has a very poor deposition effect on small particle powders and cannot achieve uniform deposition. In view of the above-mentioned problems existing in the existing double-layer coating, the inventor of this case conducted an in-depth study on the problem, which led to the creation of this case. [Summary of the invention]
[0004] The technical problem to be solved by the present invention is to provide a double-layer coated rust-proof soft magnetic powder, a coating process and a method for preparing a magnetic powder core. By combining rotary surface nitridation with rotary chemical vapor deposition technology, a dense double-layer insulating coating film is successively prepared on the surface of the soft magnetic powder, which can provide high-strength protection and insulation for the soft magnetic powder, greatly improve the rust-proof performance of the prepared magnetic powder core, and reduce the loss.
[0005] The present invention is achieved in that:
[0006] In a first aspect, a double-layer coated rust-proof soft magnetic powder comprises FeSiCr magnetic powder and a nitride layer and a SiO2 layer sequentially coated on the outer surface of the FeSiCr magnetic powder from the inside to the outside. 2 Thin film; wherein the nitride layer is formed by rotating surface nitridation coating, the SiO 2 The thin film is deposited by a rotary low-pressure chemical vapor deposition method.
[0007] In a second aspect, a coating process for double-layer coated rust-proof soft magnetic powder is provided, the coating process comprising the following steps:
[0008] Step 1, placing FeSiCr magnetic powder in a deposition tube for chemical vapor deposition, evacuating the deposition tube and introducing nitrogen;
[0009] Step 2: Use a heating device to heat the deposition tube to a preset nitriding temperature, and start the deposition tube to rotate to drive the FeSiCr magnetic powder to move;
[0010] Step 3: Introduce NH into the deposition tube 3 and H 2 The gas performs surface rotation nitriding on the FeSiCr magnetic powder within a first preset time;
[0011] Step 4. Turn off NH 3 and H 2 The gas is removed and the rotation of the deposition tube is stopped; the deposition tube is evacuated again, the deposition tube is heated to a preset deposition temperature by a heating device, and nitrogen is introduced to make the pressure in the deposition tube reach a preset deposition pressure;
[0012] Step 5, placing the ethyl orthosilicate liquid in a raw material tank, adjusting the nitrogen valve to allow nitrogen to flow through the raw material tank containing the ethyl orthosilicate liquid, and the nitrogen carries the ethyl orthosilicate liquid into the deposition tube;
[0013] Step 6: Start the deposition tube to rotate, and deposit SiO on the surface of the nitrided FeSiCr magnetic powder within the second preset time. 2 film;
[0014] Step 7: After the reaction is completed, turn off the heating equipment and the gas source valve of the ethyl orthosilicate liquid, and stop the rotation of the deposition tube; take out the FeSiCr magnetic powder after it cools down in the furnace, and a double-layer coated rust-proof soft magnetic powder can be obtained.
[0015] Furthermore, in step 1, the step of introducing nitrogen after evacuating the deposition tube is specifically as follows: evacuating the deposition tube to a vacuum degree lower than 1×10 -2 Pa, and nitrogen was introduced to maintain the pressure in the deposition tube below 50 Pa.
[0016] Furthermore, in step 2, the preset nitriding temperature is 400-650° C., and the rotation speed of the deposition tube is 10-30 r / min.
[0017] Further, in step 3, when NH 3 and H 2 When the gas is 3 and H 2 The flow rate of the gas is 50-200 ml / min, and the first preset time is 10-60 minutes.
[0018] Furthermore, in step 4, the preset deposition temperature is 700-750° C., and the preset deposition pressure is 0-150 Pa.
[0019] Furthermore, in step 6, the second preset time is 30-90 minutes.
[0020] In a third aspect, a method for preparing a magnetic powder core, the method for preparing a magnetic powder core uses a double-layer coated rust-proof soft magnetic powder, and the double-layer coated rust-proof soft magnetic powder is prepared by the coating process of the double-layer coated rust-proof soft magnetic powder according to any one of claims 2 to 7; the method for preparing a magnetic powder core comprises the following steps:
[0021] The double-layer coated anti-rust soft magnetic powder is mixed with an epoxy resin binder, and then dried and pressed to obtain a powder core green body; the pressed powder core green body is heat treated to obtain a final magnetic powder core.
[0022] Furthermore, the step of heat treating the pressed powder core green body to obtain the final magnetic powder core specifically comprises: heat treating the pressed powder core green body at 500° C. for 1 hour to obtain the final magnetic powder core.
[0023] Furthermore, the epoxy resin binder is used in an amount of 2 wt % of the weight of the double-layer coated rust-proof soft magnetic powder.
[0024] By adopting the technical solution of the present invention, at least the following beneficial effects are achieved:
[0025] 1. FeSiCr magnetic powder is selected as the powder material. During the nitriding process, Cr and N can generate CrN in situ, which is distributed at the grain boundary of α-Fe(N) on the surface of the magnetic powder and hinders the brittle Fe 4 The generation of N can improve the resistivity while maintaining the pressing characteristics. At the same time, the FeSiCr magnetic powder itself has stable magnetic permeability, high saturation magnetic induction intensity, good DC superposition characteristics, and excellent rust resistance, which helps to improve the rust resistance of the prepared magnetic powder core.
[0026] 2. By using the method of rotation combined with low-pressure chemical vapor deposition, SiO can be uniformly deposited on the outside of the nitride layer of the magnetic powder. 2 film, thus providing further protection for magnetic powder.
[0027] 3. Through the combination of rotary surface nitridation and rotary chemical vapor deposition technology, a dense double-layer insulating coating film is prepared on the surface of the magnetic powder, which can provide multiple protections for the magnetic powder, so that the coated magnetic powder has better anti-rust performance and insulation properties.
[0028] 4. The two coating processes of surface nitridation and surface deposition of magnetic powder can be completed in succession through only one furnace, without the need for multiple loading of materials. The process is simple and the preparation process is simple and convenient.
Brief Description of the Drawings
[0029] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0030] Figure 1 It is a schematic diagram of the structure of the double-layer coated FeSiCr magnetic powder provided in Example 1 of the present invention.
[0031] Figure 2 This is a morphology diagram of Example 1 of the present invention after salt atomization treatment.
[0032] Figure 3 This is a morphology diagram of comparative example 1 of the present invention after salt atomization treatment. [Specific implementation method]
[0033] The specific embodiments of the present invention will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present invention are shown in the accompanying drawings, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.
[0034] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0035] See also Figure 1-Figure 3 As shown, the present invention provides a double-layer coated rust-proof soft magnetic powder, the double-layer coated rust-proof soft magnetic powder comprises FeSiCr magnetic powder and a nitride layer and SiO2 coated sequentially on the outer surface of the FeSiCr magnetic powder from the inside to the outside. 2 Thin film; wherein the nitride layer is formed by rotating surface nitridation coating, the SiO 2 The thin film is deposited by a rotary low-pressure chemical vapor deposition method.
[0036] Compared with traditional soft magnetic materials, FeSiCr alloy has stable magnetic permeability, high saturation magnetic induction intensity, good DC superposition characteristics, and excellent rust resistance. Therefore, the present invention selects FeSiCr magnetic powder as the powder material; at the same time, during the nitriding process, Cr element and N element can in-situ generate CrN, which is distributed at the grain boundary of α-Fe(N) on the surface of the magnetic powder and hinders the brittle Fe 4 The generation of N can improve the resistivity while maintaining the pressing characteristics. The outer surface of the FeSiCr magnetic powder is coated with a nitride layer and SiO 2 The film can provide multiple protections for the magnetic powder, so that the coated magnetic powder has better anti-rust performance and insulation properties.
[0037] The present invention discloses a coating process for double-layer coated rust-proof soft magnetic powder, the coating process comprising the following steps:
[0038] Step 1, placing FeSiCr magnetic powder in a deposition tube for chemical vapor deposition, evacuating the deposition tube and introducing nitrogen, wherein the deposition tube can be a glass deposition tube; compared with traditional soft magnetic materials, the FeSiCr alloy has stable magnetic permeability, high saturation magnetic induction intensity, good DC superposition characteristics, and excellent rust resistance, so the present invention uses FeSiCr magnetic powder;
[0039] Step 2: Use a heating device to heat the deposition tube to a preset nitriding temperature, turn on the deposition tube to rotate and drive the FeSiCr magnetic powder to move, so that the FeSiCr magnetic powder is in a suspended state, so that each magnetic powder can be evenly coated; in the specific implementation of the present invention, the deposition tube can be driven to rotate by a motor drive mechanism; the heating device uses a muffle furnace;
[0040] Step 3: Introduce NH into the deposition tube 3 and H 2 The gas performs surface rotational nitriding on the FeSiCr magnetic powder within a first preset time; at high temperature, the ammonia molecules are affected by the gravitational field of the atoms on the surface of the magnetic powder and will be adsorbed on the surface of the magnetic powder, and generally the higher the temperature, the faster the adsorption; the ammonia molecules are very unstable on the surface of the magnetic powder and will decompose into nitrogen atoms and hydrogen atoms when heated, wherein the nitrogen atoms penetrate into the interior of the magnetic powder and dissolve in α-Fe to form an α-Fe(N) solid solution, i.e., a certain thickness of α-Fe(N) nitride layer is formed on the surface of the magnetic powder; at the same time, the nitrogen atoms will also react with Cr to form CrN compounds and precipitate at the grain boundaries of the Fe-N compounds;
[0041] Step 4. Turn off NH 3 and H 2 The gas is removed and the rotation of the deposition tube is stopped; the deposition tube is evacuated again, the deposition tube is heated to a preset deposition temperature by a heating device, and nitrogen is introduced to make the pressure in the deposition tube reach a preset deposition pressure;
[0042] Step 5, placing the ethyl orthosilicate liquid in a raw material tank, adjusting the nitrogen valve to allow nitrogen to flow through the raw material tank containing the ethyl orthosilicate liquid, and the nitrogen carries the ethyl orthosilicate liquid into the deposition tube;
[0043] Step 6: Start the deposition tube to rotate, so that the FeSiCr magnetic powder continues to move and is in a suspended state, so that each magnetic powder can be evenly coated, and SiO2 is deposited on the surface of the nitrided FeSiCr magnetic powder within the second preset time. 2 film;
[0044] Step 7: After the reaction is completed, turn off the heating equipment and the gas source valve of the ethyl orthosilicate liquid, and stop the rotation of the deposition tube; take out the FeSiCr magnetic powder after it cools down in the furnace, and a double-layer coated rust-proof soft magnetic powder can be obtained.
[0045] In the present invention, in step 1, the step of introducing nitrogen after evacuating the deposition tube is specifically as follows: evacuating the deposition tube to a vacuum degree of less than 1×10 -2 Pa, and nitrogen was introduced to maintain the pressure in the deposition tube below 50 Pa.
[0046] In the present invention, in step 2, the preset nitriding temperature is 400-650°C, and the rotation speed of the deposition tube is 10-30 r / min. Since the decomposition rate of ammonia is proportional to the temperature, the higher the temperature, the faster the decomposition and the faster the nitriding. However, when the temperature is higher than 700°C, ammonia will directly decompose into hydrogen and nitrogen without reacting with the magnetic powder. Therefore, the higher the nitriding temperature, the better. In addition, when the nitriding temperature is higher than 500°C, it is easy to generate Fe 4 N, although this compound has a high saturation magnetization and a large resistance, it is relatively brittle. If the pressure is too high during the subsequent magnetic powder pressing process, it is easy to cause the nitride film to rupture. When preparing components with lower pressing pressure such as one-piece molded inductors, the temperature can be increased to above 500°C during the nitriding process. Turning on the rotation of the deposition tube during nitriding and subsequent deposition can make the magnetic powder constantly reciprocate in the deposition tube, thereby increasing the contact area between the magnetic powder and the gas in the deposition tube, making the nitriding and deposition process more uniform; theoretically, increasing the rotation speed will have a better effect, but in actual application, the speed should be selected according to the specific conditions of the equipment.
[0047] In the present invention, in step 3, after introducing NH 3 and H 2 When the gas is 3 and H 2 The gas flow rate is 50-200 ml / min, and the first preset time is 10-60 minutes. The longer the nitriding time is, the thicker the nitriding layer is. Therefore, in the actual nitriding process, the thickness of the nitriding layer can be controlled by controlling the nitriding time.
[0048] In the present invention, in step 4, the preset deposition temperature is 700-750°C, and the preset deposition pressure is 0-150 Pa. Since the reaction temperature of low-pressure chemical vapor deposition is generally high, usually higher than 700°C, and the higher the temperature, the faster the deposition rate, the present invention controls the deposition temperature at 700-750°C; in addition, increasing the pressure during deposition is also conducive to obtaining a higher deposition rate, but when the pressure is too high, it will affect the content of ethyl orthosilicate, making the prepared SiO 2 The film is very loose, so the deposition pressure should not be too high. The present invention controls the deposition pressure within the range of 0 to 150 Pa, which can increase the deposition rate while ensuring the SiO 2 The quality of the film.
[0049] In the present invention, in step 6, the second preset time is 30-90 minutes. Generally speaking, the thickness of the deposited coating layer can be controlled by controlling the time of the deposition reaction. Therefore, in the actual production process, the second preset time can be adjusted according to actual needs.
[0050] The present invention provides a method for preparing a magnetic powder core, wherein the magnetic powder core preparation method uses a double-layer coated rust-proof soft magnetic powder, and the double-layer coated rust-proof soft magnetic powder is prepared by a coating process of a double-layer coated rust-proof soft magnetic powder. The coating process of the double-layer coated rust-proof soft magnetic powder is specifically described in detail above, and will not be described in detail here; the magnetic powder core preparation method comprises the following steps:
[0051] The double-layer coated anti-rust soft magnetic powder is mixed with an epoxy resin binder, dried and pressed to obtain a powder core green body; the pressed powder core green body is heat treated to obtain the final magnetic powder core.
[0052] The step of heat treating the pressed powder core green body to obtain the final magnetic powder core specifically comprises: heat treating the pressed powder core green body at 500° C. for 1 hour to obtain the final magnetic powder core.
[0053] The amount of the epoxy resin binder used is 2wt% of the weight of the double-layer coated rust-proof soft magnetic powder. It should be noted that the amount of the epoxy resin binder should not be too high, otherwise it will affect the performance of the prepared magnetic powder core. At the same time, in order to ensure that the double-layer coated rust-proof soft magnetic powder can be reliably bonded together, the amount of the epoxy resin binder should not be too small.
[0054] By adopting the above technical solution of the present invention, at least the following beneficial effects are achieved:
[0055] 1. FeSiCr magnetic powder is selected as the powder material. During the nitriding process, Cr and N can generate CrN in situ, which is distributed at the grain boundary of α-Fe(N) on the surface of the magnetic powder and hinders the brittle Fe 4 The generation of N can improve the resistivity while maintaining the pressing characteristics. At the same time, the FeSiCr magnetic powder itself has stable magnetic permeability, high saturation magnetic induction intensity, good DC superposition characteristics, and excellent rust resistance, which helps to improve the rust resistance of the prepared magnetic powder core.
[0056] 2. By using the method of rotation combined with low-pressure chemical vapor deposition, SiO can be uniformly deposited on the outside of the nitride layer of the magnetic powder. 2 film, thus providing further protection for magnetic powder.
[0057] 3. Through the combination of rotary surface nitridation and rotary chemical vapor deposition technology, a dense double-layer insulating coating film is prepared on the surface of the magnetic powder, which can provide multiple protections for the magnetic powder, so that the coated magnetic powder has better anti-rust performance and insulation properties.
[0058] 4. The two coating processes of surface nitridation and surface deposition of magnetic powder can be completed in succession through only one furnace, that is, a one-pot double-layer coating is achieved, without the need for multiple loading of materials, the process is simple, and the preparation process is simple and convenient.
[0059] The technical solution of the present invention is further described in detail below through some specific embodiments and comparative examples:
[0060] Example 1
[0061] The FeSiCr magnetic powder was placed in a deposition tube for chemical vapor deposition and the deposition tube was evacuated to 5×10 -3 After the deposition tube was heated to 400°C, the deposition tube was turned on and rotated at a rate of 25 r / min to drive the magnetic powder to move. NH 3 and H 2 Gas, the surface of FeSiCr magnetic powder was subjected to surface rotation nitridation for 30 minutes. 3 and H 2 Close the gas valve, stop the rotation of the deposition tube, evacuate the vacuum again and heat the deposition tube to 750°C so that the temperature reaches the deposition temperature, and introduce nitrogen until the pressure reaches 50Pa. Then adjust the nitrogen valve to allow nitrogen to flow through the raw material tank containing ethyl orthosilicate liquid, and the nitrogen will bring the ethyl orthosilicate liquid into the deposition tube. At the same time, turn on the deposition tube and rotate it at a rate of 25r / min. The deposition will end after 30 minutes. Turn off the heating equipment, reaction gas source and deposition tube rotation, and take out the magnetic powder after it cools down with the furnace; if Figure 1 As shown, the Figure 1 The structure diagram of the double-layer coated FeSiCr magnetic powder in Example 1 is shown. 2wt% of epoxy resin binder is added to the double-layer coated rust-proof soft magnetic powder, mixed in an acetone solution and dried, and the powder core green body is pressed at 2000MPa, and the pressed powder core green body is heat treated at 500℃ for 1 hour to obtain the final magnetic powder core.
[0062] The magnetic powder core prepared in accordance with Example 1 was subjected to performance testing, and the results were as follows:
[0063] Nitrided and SiO 2 After double coating, the magnetic permeability of the magnetic powder core is 76, which can be stabilized to 1MHz, and the loss is 1960mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 57%, and the surface of the magnetic powder core is basically free of rust after 48 hours of salt spray test. Figure 2 shown.
[0064] Example 2
[0065] The FeSiCr magnetic powder was placed in a deposition tube for chemical vapor deposition and the deposition tube was evacuated to 5×10 -3 After the deposition tube was heated to 400°C, the deposition tube was turned on and rotated at a rate of 25 r / min to drive the magnetic powder to move. NH 3 and H 2 Gas, the surface of FeSiCr magnetic powder was subjected to rotational nitridation for 20 minutes. 3 and H 2 Close the gas valve, stop the rotation of the deposition tube, evacuate the vacuum again and heat the deposition tube to 750°C, so that the temperature reaches the deposition temperature, and introduce nitrogen until the pressure reaches 50Pa. Then adjust the nitrogen valve to allow the nitrogen to flow through the raw material tank containing ethyl orthosilicate liquid, and the ethyl orthosilicate liquid is brought into the deposition tube by nitrogen. At the same time, turn on the deposition tube and rotate it at a rate of 25r / min, and the deposition is completed after 60 minutes. Turn off the heating equipment, reaction gas source and deposition tube rotation, and take out the magnetic powder after cooling with the furnace. Add 2wt% of epoxy resin binder to the double-layer coated rust-proof soft magnetic powder, mix it in acetone solution and dry it, press the powder core green body at 2000MPa, and heat treat the pressed powder core green body at 500°C for 1 hour to obtain the final magnetic powder core.
[0066] The magnetic powder core prepared in Example 2 was subjected to performance testing, and the results were as follows:
[0067] Nitrided and SiO 2 After double coating, the magnetic permeability of the magnetic powder core is 65, which can be stabilized to 1MHz, and the loss is 1820mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 68%, and the surface of the magnetic powder core has basically no rust after 48 hours of salt spray test.
[0068] Example 3
[0069] The FeSiCr magnetic powder was placed in a deposition tube for chemical vapor deposition and the deposition tube was evacuated to 5×10 -3 After the deposition tube was heated to 400°C, the deposition tube was turned on and rotated at a rate of 25 r / min to drive the magnetic powder to move. NH 3 and H 2 Gas, the surface of FeSiCr magnetic powder was subjected to surface rotation nitridation for 10 minutes. 3 and H 2Close the gas valve, stop the rotation of the deposition tube, evacuate the vacuum again and heat the deposition tube to 700°C, so that the temperature reaches the deposition temperature, and introduce nitrogen until the pressure reaches 30Pa. Then adjust the nitrogen valve to allow the nitrogen to flow through the raw material tank containing ethyl orthosilicate liquid, and the ethyl orthosilicate liquid is brought into the deposition tube by nitrogen. At the same time, turn on the deposition tube and rotate it at a rate of 25r / min, and the deposition is completed after 30 minutes. Turn off the heating equipment, reaction gas source and deposition tube rotation, and take out the magnetic powder after cooling with the furnace. Add 2wt% of epoxy resin binder to the double-layer coated rust-proof soft magnetic powder, mix it in acetone solution and dry it, press the powder core green body at 2000MPa, and heat treat the pressed powder core green body at 500°C for 1 hour to obtain the final magnetic powder core.
[0070] The magnetic powder core prepared in Example 3 was subjected to performance testing, and the results were as follows:
[0071] Nitrided and SiO 2 After double coating, the magnetic permeability of the magnetic powder core is 82, which can be stabilized to 1MHz, and the loss is 2115mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 52%, and the surface of the magnetic powder core has basically no rust after 48 hours of salt spray test.
[0072] Example 4
[0073] The FeSiCr magnetic powder was placed in a deposition tube for chemical vapor deposition and the deposition tube was evacuated to 5×10 -3 After the deposition tube was heated to 400°C, the deposition tube was turned on and rotated at a rate of 25 r / min to drive the magnetic powder to move. NH 3 and H 2 Gas, the surface of FeSiCr magnetic powder was subjected to rotational nitridation for 60 minutes. 3 and H 2Close the gas valve, stop the rotation of the deposition tube, evacuate the vacuum again and heat the deposition tube to 750°C, so that the temperature reaches the deposition temperature, and introduce nitrogen until the pressure reaches 150Pa. Then adjust the nitrogen valve to allow the nitrogen to flow through the raw material tank containing ethyl orthosilicate liquid, and the ethyl orthosilicate liquid is brought into the deposition tube by nitrogen. At the same time, turn on the deposition tube and rotate it at a rate of 25r / min, and the deposition is completed after 90 minutes. Turn off the heating equipment, reaction gas source and deposition tube rotation, and take out the magnetic powder after cooling with the furnace. Add 2wt% of epoxy resin binder to the double-layer coated rust-proof soft magnetic powder, mix it in acetone solution and dry it, press the powder core green body at 2000MPa, and heat treat the pressed powder core green body at 500°C for 1 hour to obtain the final magnetic powder core.
[0074] The magnetic powder core prepared in Example 4 was subjected to performance testing, and the results were as follows:
[0075] Nitrided and SiO 2 After double coating, the magnetic permeability of the magnetic powder core is 42, which can be stabilized to 1MHz, and the loss is 2570mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 87%, and the surface of the magnetic powder core has basically no rust after 48 hours of salt spray test.
[0076] Comparative Example 1
[0077] The FeSiCr magnetic powder is directly mixed with epoxy resin and acetone solution, the amount of epoxy resin used is 3wt% of the weight of the FeSiCr magnetic powder, and the mixture is dried after being fully stirred; the powder core green body is pressed at 2000MPa, and the pressed powder core green body is heat treated at 500℃ for 1 hour to obtain an epoxy resin-coated magnetic powder core.
[0078] The magnetic powder core prepared in Comparative Example 1 was subjected to performance testing, and the results are as follows:
[0079] After epoxy resin coating, the magnetic powder core has a magnetic permeability of 82, which can be stabilized to 1MHz, and the loss is 3050mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 42%. After 48 hours of salt spray test, the surface of the magnetic powder core is corroded in a large area. Figure 3 shown.
[0080] Comparative Example 2
[0081] The FeSiCr magnetic powder is directly mixed with epoxy resin, silicone resin and acetone solution, the amount of epoxy resin and silicone resin is 1.5wt% of the weight of the FeSiCr magnetic powder, and the mixture is fully stirred and dried; the powder core green body is pressed at 2000MPa, and the pressed powder core green body is heat treated at 500℃ for 1 hour to obtain a magnetic powder core coated with epoxy resin and silicone resin.
[0082] The magnetic powder core prepared in Comparative Example 2 was subjected to performance testing, and the results were as follows:
[0083] After being coated with two kinds of resins, the magnetic permeability of the magnetic powder core is 75, which can be stabilized to 1MHz, and the loss is 2890mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 46%. After 48 hours of salt spray test, a large area of the surface of the magnetic powder core is rusted.
[0084] Comparative Example 3
[0085] The FeSiCr magnetic powder is directly mixed with nano-SiO 2 The particles are mixed in an alcohol solution, and the nano-SiO 2 The amount of particles is 0.5wt% of the weight of FeSiCr magnetic powder; epoxy resin and acetone solution are added and mixed, the amount of epoxy resin is 2wt% of the weight of FeSiCr magnetic powder, and the mixture is fully stirred and dried; the powder core green body is pressed at 2000MPa, and the pressed powder core green body is heat treated at 500℃ for 1 hour to obtain a magnetic powder core composite-coated with silica and epoxy resin.
[0086] The magnetic powder core prepared in Comparative Example 3 was subjected to performance testing, and the results are as follows:
[0087] After being coated with nano-silicon dioxide and epoxy resin, the magnetic permeability of the magnetic powder core is 74, which can be stabilized to 1MHz, and the loss is 2680mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 52%. The surface of the magnetic powder core is partially corroded after 48 hours of salt spray test.
[0088] Comparative Example 4
[0089] The FeSiCr magnetic powder is directly mixed with phosphoric acid in an alcohol solution, wherein the amount of phosphoric acid is 0.5wt% of the weight of the FeSiCr magnetic powder, and the mixture is fully stirred and dried. An epoxy resin and an acetone solution are added and mixed, wherein the amount of the epoxy resin is 2wt% of the weight of the FeSiCr magnetic powder, and the mixture is fully stirred and dried. A powder core green body is pressed at 2000MPa, and the pressed powder core green body is heat treated at 500°C for 1 hour to obtain a magnetic powder core composite-coated with silica and epoxy resin.
[0090] The magnetic powder core prepared in Comparative Example 4 was subjected to performance tests, and the results were as follows:
[0091] After phosphating coating, the magnetic permeability of the magnetic powder core is 78, which can be stabilized to 1MHz, and the loss is 2465mW / cm under the conditions of 0.1T and 200kHz. 3 , the DC bias performance under 100Oe is 50%, and the surface of the magnetic powder core is partially corroded after 48 hours of salt spray test.
[0092] It can be seen from the above comparison that the one-pot double-layer coating technical solution of the present invention can effectively improve the rust resistance of the magnetic powder core, improve the insulation properties, and reduce high-frequency losses compared with the prior art solutions.
[0093] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A double-layer coated rust-proof soft magnetic powder, characterized in that: The double-layer coated rust-proof soft magnetic powder includes FeSiCr magnetic powder and a nitride layer and a SiO2 film sequentially coated on the outer surface of the FeSiCr magnetic powder from the inside to the outside; wherein the nitride layer is formed by rotating surface nitridation coating, and the SiO2 film is formed by rotating low-pressure chemical vapor deposition deposition coating.
2. A double-layer coating process for rust-proof soft magnetic powder, characterized in that: The coating process comprises the following steps: Step 1, placing FeSiCr magnetic powder in a deposition tube for chemical vapor deposition, evacuating the deposition tube and introducing nitrogen; Step 2: Use a heating device to heat the deposition tube to a preset nitriding temperature, and start the deposition tube to rotate to drive the FeSiCr magnetic powder to move; Step 3, introducing NH3 and H2 gases into the deposition tube to perform surface rotation nitridation on the FeSiCr magnetic powder within a first preset time; Step 4, turn off the NH3 and H2 gases, and stop the rotation of the deposition tube; evacuate the deposition tube again, use a heating device to heat the deposition tube to a preset deposition temperature, and introduce nitrogen gas to make the pressure in the deposition tube reach a preset deposition pressure; Step 5, placing the ethyl orthosilicate liquid in a raw material tank, adjusting the nitrogen valve to allow nitrogen to flow through the raw material tank containing the ethyl orthosilicate liquid, and the nitrogen carries the ethyl orthosilicate liquid into the deposition tube; Step 6, start the rotation of the deposition tube to deposit a SiO2 film on the surface of the nitrided FeSiCr magnetic powder within a second preset time; Step 7: After the reaction is completed, turn off the heating equipment and the gas source valve of the ethyl orthosilicate liquid, and stop the rotation of the deposition tube; take out the FeSiCr magnetic powder after it cools down in the furnace, and a double-layer coated rust-proof soft magnetic powder can be obtained.
3. A coating process for double-layer coated rust-proof soft magnetic powder as claimed in claim 2, characterized in that: In step 1, the step of introducing nitrogen into the deposition tube after evacuating the deposition tube is specifically as follows: the vacuum degree of the deposition tube is evacuated to less than 1×10 -2 Pa, and nitrogen was introduced to maintain the pressure in the deposition tube below 50 Pa.
4. A coating process for double-layer coated rust-proof soft magnetic powder as claimed in claim 2, characterized in that: In the step 2, the preset nitriding temperature is 400-650° C., and the rotation speed of the deposition tube is 10-30 r / min.
5. A coating process for double-layer coated rust-proof soft magnetic powder as claimed in claim 2, characterized in that: In the step 3, when NH3 and H2 gases are introduced, the flow rate of the NH3 and H2 gases is 50-200 ml / min, and the first preset time is 10-60 minutes.
6. A coating process for double-layer coated rust-proof soft magnetic powder as claimed in claim 2, characterized in that: In the step 4, the preset deposition temperature is 700-750° C., and the preset deposition pressure is 0-150 Pa.
7. A coating process for double-layer coated rust-proof soft magnetic powder as claimed in claim 2, characterized in that: In step 6, the second preset time is 30-90 minutes.
8. A method for preparing a magnetic powder core, characterized in that: The magnetic powder core preparation method uses double-layer coated rust-proof soft magnetic powder, and the double-layer coated rust-proof soft magnetic powder is prepared by the coating process of the double-layer coated rust-proof soft magnetic powder according to any one of claims 2 to 7; the magnetic powder core preparation method comprises the following steps: The double-layer coated anti-rust soft magnetic powder is mixed with an epoxy resin binder, and then dried and pressed to obtain a powder core green body; the pressed powder core green body is heat treated to obtain a final magnetic powder core.
9. A method for preparing a magnetic powder core according to claim 8, characterized in that: The step of heat treating the pressed powder core green body to obtain the final magnetic powder core specifically comprises: heat treating the pressed powder core green body at 500° C. for 1 hour to obtain the final magnetic powder core.
10. A method for preparing a magnetic powder core according to claim 8, characterized in that: The amount of the epoxy resin binder is 2 wt % of the weight of the double-layer coated rust-proof soft magnetic powder.
Citation Information
Patent Citations
Double-layer inorganic insulation coated soft magnetic powder and preparation method thereof
CN109979701A
A rust-resistant, high-performance soft magnetic metal powder and its preparation method
CN117275927B